Algebra Examples
3x+4x-6+x5-x3+4x2-3x+6x5=03x+4x−6+x5−x3+4x2−3x+6x5=0
Step 1
Step 1.1
Combine the opposite terms in 3x+4x-6+x5-x3+4x2-3x+6x53x+4x−6+x5−x3+4x2−3x+6x5.
Step 1.1.1
Subtract 3x3x from 3x3x.
4x-6+x5-x3+4x2+0+6x5=04x−6+x5−x3+4x2+0+6x5=0
Step 1.1.2
Add 4x-6+x5-x3+4x24x−6+x5−x3+4x2 and 00.
4x-6+x5-x3+4x2+6x5=04x−6+x5−x3+4x2+6x5=0
4x-6+x5-x3+4x2+6x5=04x−6+x5−x3+4x2+6x5=0
Step 1.2
Add x5x5 and 6x56x5.
4x-6+7x5-x3+4x2=04x−6+7x5−x3+4x2=0
4x-6+7x5-x3+4x2=04x−6+7x5−x3+4x2=0
Step 2
Graph each side of the equation. The solution is the x-value of the point of intersection.
x≈0.723681x≈0.723681
Step 3